JAK/STAT/SOCS‐signaling pathway and colon and rectal cancer1. Issue 2 (28th November 2011) - Slattery, Martha L.; Lundgreen, Abbie; Kadlubar, Susan A.; Bondurant, Kristina L.; Wolff, Roger K.
Abstract The Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway is involved in immune function and cell growth. We evaluated the association between genetic variation in JAK1 (10 SNPs), JAK2 (9 SNPs), TYK2 (5 SNPs), suppressors of cytokine signaling (SOCS)1 (2 SNPs), SOCS2 (2 SNPs), STAT1 (16 SNPs), STAT2 (2 SNPs), STAT3 (6 SNPs), STAT4 (21 SNPs), STAT5A (2 SNPs), STAT5B (3 SNPs), STAT6 (4 SNPs) with risk of colorectal cancer. We used data from population‐based case‐control studies (colon cancer n = 1555 cases, 1, 956 controls; rectal cancer n = 754 cases, 959 controls). JAK2, SOCS2, STAT1, STAT3, STAT5A, STAT5B, and STAT6 were associated with colon cancer; STAT3, STAT4, STAT6, and TYK2 were associated with rectal cancer. Given the biological role of the JAK/STAT‐signaling pathway and cytokines, we evaluated interaction with IFNG, TNF, and IL6; numerous statistically significant associations after adjustment for multiple comparisons were observed. The following statistically significant interactions were observed: TYK2 with aspirin/NSAID use; STAT1, STAT4, and TYK2 with estrogen status; and JAK2, STAT2, STAT4, STAT5A, STAT5B, and STAT6 with smoking status and colon cancer risk; JAK2, STAT6, and TYK2 with aspirin/NSAID use; JAK1 with estrogen status; STAT2 with cigarette smoking and rectal cancer. JAK2, SOCS1, STAT3, STAT5, and TYK2 were associated with colon cancer survival (hazard rate ratio (HRR) of 3.3 95% CI 2.01, 5.42 for high mutational load). JAK2, SOCS1, STAT1, STAT4, and TYK2 were associated with rectal cancer survival (HRR 2.80 95% CI 1.63, 4.80). These data support the importance of the JAK/STAT‐signaling pathway in colorectal cancer and suggest targets for intervention. © 2011 Wiley Periodicals, Inc.